A comprehensive estimation method of phase error in the frequency‐interleaving digital‐to‐analog converter. Issue 2 (14th January 2023) - Zhao, Wenhao; Tian, Shulin; Liu, Ke; Xiao, Yindong
Abstract: This letter studied the phase error in the frequency‐interleaving digital‐to‐analog converter (FI‐DAC) and proposed a comprehensive phase estimation method. Firstly, the model of the FI‐DAC system was established, and the phase error was considered that consists of three parts: time delay error, initial phase error and non‐linear phase error. By analyzing the phase function characteristics of the system, the least squares (LS) was used to linearly fit the phase functions of the non‐overlapping bands to estimate both the time delay and the initial phase of each sub‐band channel. Then, the non‐linear phase error of the system was estimated by the difference between the system phase function and the estimated linear phase function. Finally, the effectiveness of the proposed estimation method was verified by the built FI‐DAC test bench. Abstract : This letter studied the phase error in the frequency‐interleaving digital‐to‐analog converter (FI‐DAC) and proposed a comprehensive phase estimation method.